MANAJEMEN BEBAN KERJA GURU BERBASIS DATA DAN BERKEADILAN DI SEKOLAH - Didit Darmawan; Achmad Choirul Anwar; Abd Ghofur; Ronal Abiyyu; Anshorullah (STAI Nusantara Kota Banda Aceh, 2026)
This article develops a conceptual examination of data based and fair workload management for teachers in schools. It argues that teaching hours represent only one component of teachers’ work, alongside administrative obligations, additional assignments, student guidance, and professional development activities. The paper proposes that schools design a comprehensive workload classification, assign relative weights to different task categories, and record all activities in a digital system. Such a system enables systematic analysis of task distribution across staff and supports decisions that aim to avoid overburdening individual teachers. The discussion highlights the need to align workload policies with work life balance considerations, so that teachers can maintain well being while sustaining high quality teaching. Leadership commitment, transparency, and structured dialogue between teachers and school management are emphasised as key conditions for implementing data informed workload policies. The framework presented here is intended as a theoretical basis for schools and policy makers who seek to organise teacher assignment more fairly and sustainably.